A ring accelerator? Unusual jet dynamics in the IceCube candidate PKS 1502+106. Issue 3 (17th March 2021) - Britzen, S; Zajaček, M; Popović, L Č; Fendt, C; Tramacere, A; Pashchenko, I N; Jaron, F; Pánis, R; Petrov, L; Aller, M F; Aller, H D
ABSTRACT: On 2019/07/30.86853 ut, IceCube detected a high-energy astrophysical neutrino candidate. The Flat Spectrum Radio Quasar PKS 1502+106 is located within the 50 per cent uncertainty region of the event. Our analysis of 15 GHz Very Long Baseline Array (VLBA) and astrometric 8 GHz VLBA data, in a time span prior and after the IceCube event, reveals evidence for a radio ring structure that develops with time. Several arc-structures evolve perpendicular to the jet ridge line. We find evidence for precession of a curved jet based on kinematic modelling and a periodicity analysis. An outflowing broad line region (BLR) based on the C iv line emission (Sloan Digital Sky Survey) is found. We attribute the atypical ring to an interaction of the precessing jet with the outflowing material. We discuss our findings in the context of a spine-sheath scenario where the ring reveals the sheath and its interaction with the surroundings (narrow line region, NLR, clouds). We find that the radio emission is correlated with the γ-ray emission, with radio lagging the γ-rays. Based on the γ-ray variability time-scale, we constrain the γ-ray emission zone to the BLR (30–200 r g ) and within the jet launching region. We discuss that the outflowing BLR provides the external radiation field for γ-ray production via external Compton scattering. The neutrino is most likely produced by proton–proton interaction in the blazar zone (beyond the BLR), enabled by episodic encounters of the jet with dense clouds, i.e. some molecular cloud in the NLR.